An Analysis of EFL Students™ Speaking Anxiety Factors in Speaking in Formal Context Class - Mardiah, Henny (Universitas Negeri Medan, 2023)
This study investigated speaking anxiety factors that lead EFL (English as a Foreign Language) students feel anxious in Speaking in Formal Context class. The participants of this research were 29 students of class B1, 2nd semester, English Education Department of Universitas Muhammadiyah Sumatera Utara , even semester, academic year 2022-2023. This research was conducted with descriptive qualitative approach by administering questionnaires to students which consisted of five closed-ended questions. The questions were taken from FLSAS questionnaires. Observation was also applied to this study. Lecturer observed the progress of students™ speaking performances from the second meeting until the last regular meeting. The findings revealed that students™ speaking anxiety factors in English speaking class mainly dominated by the lack abilities in vocabulary, pronunciation, grammar, worried of being laughed at by peers which resulted to the anxiety, inconfidence and fear in speaking. These findings suggest that the lecturer™s role is also significant to encourage